Serum Cortisol and Clinical Response to a Single Session of Whole-Body Vibration in Healthy Adult Dogs - Tannus, Filipe C. I.; Rahal, Sheila C.; Oba, Eunice; Tsunemi, Miriam; Silva, Bruna M.; Almeida, Karina C.; Santos, Ivan F. C. (Frontiers in Veterinary Science, 2021)
This study evaluated the serum cortisol response to a single session of WBV in healthy adult dogs. Ten healthy adult medium dogs, females and males, aged between 24 and 48-months old and body weight between 10.1 and 17.9 kg were used. Single WBV session at frequency of 30 Hz frequency for 5 min (3.10 mm peak displacement; 11.16 m/s2 peak acceleration; 0.29 m/s velocity), then 50 Hz for 5 min (3.98 mm peak displacement; 39.75 m/s2 peak acceleration; 0.62 m/s velocity), and finishing with 30 Hz for 5 min (3.10 mm peak displacement; 11.16 m/s2 peak acceleration; 0.29 m/s velocity) was performed. Serum cortisol, heart, and respiratory rate and systolic blood pressure were evaluated at different time-points: 1 min before the WBV (1PRE), 1 min after WBV (1POST), 60 (60POST) and 360 min after WBV session (360POST). An increase (P = 0.0417) of serum cortisol values was observed between 1PRE and 1POST; and decrease (P = 0.0417) between 1POST and 60POST; and between 60POST and 360POST. However, the values remained within the reference range. Heart and respiratory rate, systolic blood pressure remained unchanged. Our findings suggest that a single bout of WBV (5-min of 30 and 50 Hz) by using a vibrating platform that delivered a vortex wave circulation does not modify serum cortisol levels and clinical parameters of healthy adult dogs.